The Impact of the Application of Artificial Intelligence Technology on the Design Practice of Sports Visual Communication - Lyu, Jinlong; Peng, Luyao (Journal of Electrical Systems, 2024)
With the rapid development and application of artificial intelligence (AI) technology, the field of sports visual communication is undergoing unprecedented changes. This paper aims to explore the application of AI technology in the practice of sports visual design, and its impact on visual communication effects and design processes. Through the innovative application of sports visual elements and the optimization of visual design processes, this paper reveals how AI technology can improve the efficiency and quality of sports visual communication, and also points out the challenges and limitations it brings. It is of great significance to promote technological innovation and design improvement in the field of sports visual communication and also provides useful inspiration for exploring the application of AI technology in a wider field of visual design.